Perceived Institutional Restraint Is Associated With Psychological Distress in Forensic Psychiatric Inpatients - Franke, Irina; Büsselmann, Michael; Streb, Judith; Dudeck, Manuela (Frontiers in Psychiatry, 2019)
Background: Patients in forensic mental health care experience internal and external coercion; the latter comprises different levels of institutional restraint. These restrictions of individual freedom are mainly justified by the safety interests of third parties and are not necessarily in the patients’ best interests. The effects of such a setting on mentally disordered offenders’ psychological state and treatment course are not fully understood. Assessing both patients’ perception of restraint and psychopathological symptoms would allow us to better understand how restraint and psychopathology interact and how they might influence treatment. Methods: In 184 forensic psychiatric inpatients, we assessed perception of institutional restraint with an adapted version of the Measuring the Quality of Prison Life (aMQPL) questionnaire and current psychological state with the Brief Symptom Checklist (BSCL) and Beck Hopelessness Scale (BHS). Results: Perceived institutional restraint (as expressed in the aMPQL subscales Transparency of procedures and decisions, Fairness, and Respect) was associated with a higher general level of psychological symptoms. Furthermore, patients who perceived a lack of institutional transparency and respect were more likely to have higher scores for hostility, depression, and suicidal ideation. We also found age and sex differences, with higher levels of psychological symptoms in younger and female patients. The diagnosis and duration of detention did not relate to perceived restraint. Discussion: Our results indicate that certain aspects of institutional restraint in long-term forensic inpatient settings correlate with certain psychological symptoms. The observed association might be explained by different kinds of factors: institutional (custodial focus), individual (self-efficacy, diagnosis, personality), and situational (duration of detention). Although not all of these explanatory factors were addressed by the present study design, forensic mental health professionals should be aware of the relationship between perceived institutional restriction and psychopathology because it might influence treatment course and outcome.